PERSEPSI AKAN TEKANAN TERHADAP KESEJAHTERAAN PSIKOLOGIS PADA PASANGAN SUAMI-ISTRI DENGAN STROKE - Novia Ayuningputri; Herdiyan Maulana (Journal of Research and Measurement in Psychology, 2013)
Abstract This study was conducted to determine the effect of perceptions of caregiver strain and psychological well-being of wives or husbands as providers of care for his partner who had a stroke. Field studies in this research lasted from April to June 2013. This study using quantitative methods with ex post facto research design and using accidental sampling techniques. Participants in this study amounted to 37 wives or husbands of stroke patients who have taken role as spouse caregiver for at least 3 months. The participants were found at the clubs stroke and stroke rehabilitation center in Jakarta. The data was collected using a measuring instrument that has been adapted into Indonesian. The Modified Caregiver Strain Index is consisting of 13 items and Ryff's Psychological Well-being Scale consisting of 54 items. Based on the results of the data, obtained value of F = 0.085, p = 0.772> 0:05 (not significant) and the value effect (Adjusted R Square) 2.6%. So that it can be concluded that there is no significant effect of Perception Towards Caregiver strain on psychological well-being by by wives or husbands who became spouse caregiver for their partner who had suffered from stroke. Keywords: Caregiver strain, Spouse caregiver, Stroke patients, Psychological well-being.